Investigation on the contour and bone mineral density of the distal tibial cutting surface used for total ankle arthroplasty. (30th June 2021) - Zhao, Dahang; Zhang, Gonghao; Huang, Dichao; Yu, Jian; Wang, Kan; Wang, Xu; Zhang, Tiansong; Ma, Xin
Purpose: This study was designed to investigate (1) the contour of the distal tibial cutting surface, and (2) the bone mineral density (BMD) of the distal tibial cutting surface used during total ankle arthroplasty (TAA). Methods: Eight-four distal tibial models were created using foot and ankle computerized tomographic (CT) images taken from normal people. The distal tibial cutting surface for TAA was determined to be 10 mm proximal to the tibial plafond. The bony contour and BMD values were determined from the CT image at that level. A bounding box was made on the contour and the width and length of the contour was measured. Regional BMD was evaluated by Hounsfield units (HU) value measurement, with 7 regions of interest (ROI) on 8 different directions for all the 84 CT images. Two different observers made independent measurements and mean HU values for all the 56 ROIs were calculated. Results: Great variations were found among the contours of the cutting surface especially in term of the shape of the anterior and posterior tibial tubercle, and the fibular notch. These variations could be grouped into six categories. For the BMD of the cutting surface, the medial border of the cutting surface did not included cortical bone. The HU value of seven ROIs, which included cortical bone, were significantly greater than all the other ROIs. Few statistical differences were found by multiple comparisons among HU value of all the 49 ROIs without cortex. Conclusions: Great variability existed in the shape and the BMD of the distal tibial cutting surface.